TEACHER MISCONCEPTIONS IN DEEP LEARNING ORIENTED INSTRUCTION AND THEIR REMEDIATION THROUGH INSTRUCTIONAL MODULES AND COLLABORATIVE MENTORING - Buniahe, Ridwain Stepi; Rorimpandey, Widdy H.F; Monigir, Norma (SOSIOEDUKASI, 2026)
This study is grounded in the persistent presence of pedagogical misconceptions among teachers in implementing deep learning–oriented instruction, which leads to inaccuracies in both instructional design and classroom practice. These misconceptions extend beyond technical issues and reflect deeper conceptual misunderstandings, particularly in relation to learning principles, learning experiences, instructional syntax, and the integration of digital technologies. This study aims to identify the forms of teachers’ pedagogical misconceptions and to examine how these can be addressed through instructional modules and collaborative mentoring. A qualitative approach was employed, with data collected through classroom observations, in-depth interviews, and document analysis. Data were analyzed using an interactive model involving data reduction, data display, and conclusion drawing. The findings reveal that teachers’ pedagogical misconceptions are structural in nature and manifest across multiple dimensions of instruction. Teachers tend to conflate learning principles with learning activities, interpret learning experiences merely as sequences of tasks, organize instructional syntax in a fragmented manner, and utilize digital technology in a predominantly instrumental way. The intervention, implemented through instructional modules and collaborative mentoring, demonstrates a gradual yet transformative improvement in teachers’ pedagogical understanding. This study concludes that addressing pedagogical misconceptions requires an integrated approach that combines conceptual reinforcement with reflective processes facilitated through collaborative mentoring.